Yearning for affection: Traumatic bonding between Korean 'comfort women' and Japanese soldiers during World War II. Issue 4 (November 2019) - Ahn, Yonson
This work analyses the complex and contentious issues of mutual affection and codependency in relationships between Korean 'comfort women' and Japanese soldiers during World War II. Drawing on a combination of interviews and published resources, it explores the groups' perceptions of one another within the framework of 'traumatic bonding'. Despite traumatic violence and stark inequalities, this article finds nuanced contributions from the parties involved. For the soldiers, the relationships provided a form of emotional relief from the violence of war and from the oppression they themselves were subjected to by those of superior rank within the military hierarchy, while the women often sought kindness and protection from the military men with whom they had formed relationships. However, underneath the yearning for human connection, these relationships were highly complex and deeply affected by the overarching power dynamics of gender and the racialised colonial hierarchy.